2023
DOI: 10.1038/s41467-023-37937-4
|View full text |Cite|
|
Sign up to set email alerts
|

Patterns in soil microbial diversity across Europe

Abstract: Factors driving microbial community composition and diversity are well established but the relationship with microbial functioning is poorly understood, especially at large scales. We analysed microbial biodiversity metrics and distribution of potential functional groups along a gradient of increasing land-use perturbation, detecting over 79,000 bacterial and 25,000 fungal OTUs in 715 sites across 24 European countries. We found the lowest bacterial and fungal diversity in less-disturbed environments (woodland… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 106 publications
2
25
1
Order By: Relevance
“…Compared to woodlands, (croplands also contained significantly higher diversity and richness of tardigrades, nematodes, arthropods, and annelids) and higher richness of rotifers. Although this finding contrasts with previous observations of consistent declines in soil biodiversity with increasing land use intensity (Schulz et al, 2019; Tsiafouli et al, 2015), it is in line with recent analyses of microbial communities from the same LUCAS soil samples (16S bacteria and ITS fungi; Labouyrie et al, 2023) indicating that ecosystem type is the main driver shaping the whole soil food web. β‐diversity was also strongly shaped by ecosystem type, in agreement with previous studies that compared grasslands and forests in the Amazonas (Ritter et al, 2019) and those investigating the effects of vegetation on bacterial and microeukaryotic communities in the arctic tundra (Shi et al, 2015).…”
Section: Discussioncontrasting
confidence: 82%
“…Compared to woodlands, (croplands also contained significantly higher diversity and richness of tardigrades, nematodes, arthropods, and annelids) and higher richness of rotifers. Although this finding contrasts with previous observations of consistent declines in soil biodiversity with increasing land use intensity (Schulz et al, 2019; Tsiafouli et al, 2015), it is in line with recent analyses of microbial communities from the same LUCAS soil samples (16S bacteria and ITS fungi; Labouyrie et al, 2023) indicating that ecosystem type is the main driver shaping the whole soil food web. β‐diversity was also strongly shaped by ecosystem type, in agreement with previous studies that compared grasslands and forests in the Amazonas (Ritter et al, 2019) and those investigating the effects of vegetation on bacterial and microeukaryotic communities in the arctic tundra (Shi et al, 2015).…”
Section: Discussioncontrasting
confidence: 82%
“…These results indicate that fertilisation rather than defoliation has potential to stimulate soil bacterial and fungal communities without altering soil microbial community structure, as also found by others (Fanin et al., 2015; Li et al., 2020; Liang et al., 2011). However, previous studies have reported that fertiliser application, especially of phosphorus, can decrease the diversity and abundance of arbuscular mycorrhizal fungi, which influences phosphorus transfer from microbes to host plants, as well as long‐term SOM accumulation via melanised hyphae (Frater et al., 2018; Labouyrie et al., 2023; Oelmann et al., 2021; Ryan & Graham, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…7°to 13°C (i.e., optimal for most plants and ectotherms and fungal pathogens' primary hosts) while sharply declining outside this range (i.e., in extreme hyper-arid, alpine, and Arctic habitats). These findings, summarizing the variety of relationships between pathogen diversity and host community properties (36)(37)(38)(39), suggest that a biotic community exceeding a certain low threshold of diversity or biomass invariably shelters a relatively diverse community of fungal pathogens.…”
Section: Alpha Diversity Of Fungal Ecological Groupsmentioning
confidence: 92%